2018
DOI: 10.1002/jrs.5360
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Raman spectroscopy of breast tumors prephotodynamic and postphotodynamic therapy

Abstract: Breast cancer is most fatal cancer among women worldwide. The high mortality can be attributed to late detection and low treatment efficacy. Treatment is difficult owing to the multitude of breast cancer subtypes and making decisions on therapeutic strategy difficult. A tool to predict treatment prognosis may greatly aid this decision making. Currently available prediction methods have low accuracy in addition to several other disadvantages. Of the several new techniques being investigated for prognosis predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The relative increase in some spectral signatures associated with nucleic acids, amino acids, proteins, and especially collagen, were observed posttherapy; and pretherapy and posttherapy spectra could be classified with 100% efficiency. The ability of Raman spectroscopy to detect these changes suggests the possibility of deciphering spectral markers for prognostic applications in the future . Dai et al used Raman scattering to discriminate between oral cancer and healthy cells based on the adenine signature.…”
Section: Biosciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative increase in some spectral signatures associated with nucleic acids, amino acids, proteins, and especially collagen, were observed posttherapy; and pretherapy and posttherapy spectra could be classified with 100% efficiency. The ability of Raman spectroscopy to detect these changes suggests the possibility of deciphering spectral markers for prognostic applications in the future . Dai et al used Raman scattering to discriminate between oral cancer and healthy cells based on the adenine signature.…”
Section: Biosciencesmentioning
confidence: 99%
“…The ability of Raman spectroscopy to detect these changes suggests the possibility of deciphering spectral markers for prognostic applications in the future. [74] Dai et al used Raman scattering to discriminate between oral cancer and healthy cells based on the adenine signature. They find that the detection of adenine Raman signals from cell lines has been proven to have the potential to establish a highly distinguishable Raman diagnostic method for cancer detection.…”
Section: Biomoleculesmentioning
confidence: 99%
“…To clarify the biochemical mechanisms of cancer treatment, Fox et al used Raman spectroscopy combined with multivariate analysis to classify normal and cancerous skin tissue, and evaluated the differences between tissues treated with high energy CO 2 laser and untreated tissue [25]. In studies of the spectral variations of breast cancer tissues pre-and post-photodynamic therapy in animal models, Fontana et al revealed the underlying mechanisms for the variations of biochemical components in cancerous tissues after PDT treatment [26]. Raman spectroscopy has also been used for prognostic evaluations, such as in vitro radiation responses in human tumor cells, radiotherapy responses in patients with cervical cancer, and radiation damage in mouse brain [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…55,56 In vivo, Bhattacharjee et al performed RS measurements in breast cancer model rats showing PS accumulation and PDT effects of chlorin photodithazine. 57 An alternative approach is to use Surface-Enhanced RS (SERS) to increase the limit of detection of the PS, often done by including metal nanoparticles in theranostic constructs with the PS. [58][59][60][61][62][63][64] Fales et al, used targeted gold nanostar constructs loaded with PPIX, showing detection and targeting in single cells, 65,66 and Farhadi et al coupled palladium porphyrin with plasmonic nanoparticles to allow SERS detection of the PS, using the same wavelength to excite Raman scattering and to stimulate PDT.…”
Section: Introductionmentioning
confidence: 99%